2021
DOI: 10.1073/pnas.2108395118
|View full text |Cite
|
Sign up to set email alerts
|

How immunity from and interaction with seasonal coronaviruses can shape SARS-CoV-2 epidemiology

Abstract: We hypothesized that cross-protection from seasonal epidemics of human coronaviruses (HCoVs) could have affected severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) transmission, including generating reduced susceptibility in children. To determine what the prepandemic distribution of immunity to HCoVs was, we fitted a mathematical model to 6 y of seasonal coronavirus surveillance data from England and Wales. We estimated a duration of immunity to seasonal HCoVs of 7.8 y (95% CI 6.3 to 8.1) and show t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 62 publications
2
16
0
Order By: Relevance
“…We observed that about 72-81% of subjects exhibited immune CD4+ T cell memory responses to each of the 4 CCC studied, consistent with frequencies detected in both community and heath care works cohorts 26 , and similar to the findings of Tan et al 25 . Remarkably, we found a stable and sustained T cell and antibody response against CCC which are supported by recent experimental findings from Cohen et al 41 or mathematical modeling 19,20 and argues against the short-lived nature of CCC responses 1618 . Our findings are also in agreement with the stability of responses against other viral infections, such as vaccinia or SARS-CoV-1 where antigen specific cells were detectable 50 years and 17 years post infection, respectively 47,48 and against TT which are remarkably stable for many years upon vaccination 49 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We observed that about 72-81% of subjects exhibited immune CD4+ T cell memory responses to each of the 4 CCC studied, consistent with frequencies detected in both community and heath care works cohorts 26 , and similar to the findings of Tan et al 25 . Remarkably, we found a stable and sustained T cell and antibody response against CCC which are supported by recent experimental findings from Cohen et al 41 or mathematical modeling 19,20 and argues against the short-lived nature of CCC responses 1618 . Our findings are also in agreement with the stability of responses against other viral infections, such as vaccinia or SARS-CoV-1 where antigen specific cells were detectable 50 years and 17 years post infection, respectively 47,48 and against TT which are remarkably stable for many years upon vaccination 49 .…”
Section: Discussionsupporting
confidence: 90%
“…Whether immunity to CCC viruses is short or long lived has been debated with conflicting reports [16][17][18][19][20][21][22] . Some discrepancies may be reconciled as some reports consider immunity as protection from re-infection while others consider protection from symptomatic disease.…”
Section: Introductionmentioning
confidence: 99%
“…HCoV-229E and HCoV-NL63, or betacoronaviruses, i.e. HCoVHKU1 and HCoV-OC43; SARS-CoV, MERS-CoV, and SARS-CoV-2 belong to the betacoronavirus genera (199).…”
Section: Previous Infection With Seasonal Coronavirusesmentioning
confidence: 99%
“…Though the LPH-CoVs induced antibody response is short-lasting and has limited protection from hosts infected by the same or different common cold coronaviruses ( 8 ), it is hypothesized that the cross-reactive antibodies response from prior LPH-CoVs exposure could have reduced the susceptibility and possibility of developing severe clinical syndrome on SARS-CoV-2 infection in children ( 12 , 13 ). However, studies exploring whether the pre-existing antibodies induced by LPH-CoVs can cross-react with SARS-CoV-2 generate conflicting results.…”
Section: Introductionmentioning
confidence: 99%